(untitled) (Revista Brasileira Multidisciplinar, 2024)
This study focuses on the problem of invasive species, wich are introduced by human activities and can have serious negative impacts on ecosystems. This problem is becoming more urgent due to factors such as habitat fragmentation, urban expansion, ecosystem changes, and globalization. In this way, the introduction of species is considered as the second biggest cause responsible for the extinction of species, behind only the destruction of habitats. In this sense, understanding the dynamics of the process of invasion and the establishment of an exotic species as an invasive species, as well as the identification of which species found in Brazil are considered invasive, is extremely important, since such species directly impact the maintaining the diversity of native species and significantly affect the ecological succession and the Community ecology. The list considered both ‘green areas’ and forest remnants, as well, the anthropized areas. As a result, a list of 27 distinct species was obtained, among mammals, birds, fish and invertebrates (Hexapoda, annelida and Mollusca), which were evaluated according to their potential to become invasive species at the site (potential invasive species: ‘Low’, ‘Moderate’, ‘High’ and ‘Very High’). From this list, the situation of each species was analyzed individually, considering the reality of the local context and the literature, in order to discuss the processes and impacts involved if the species becomes invasive. Finally, the increase in the presence of exotic and synanthropic species on the campus was related to the growth of urban areas in the region and surroundings, presenting arguments about how human activity influences the dispersion and, the consolidation of certain species as invasive. It also addresses which measures can help prevent or combat the impact of biological pollution on natural ecosystems. The use of the campus as a ’microcosm’ leads to discussion of what measures can help prevent or combat the impact of ‘Biological Pollution’.